2024
DOI: 10.1136/ijgc-2023-004557
|View full text |Cite
|
Sign up to set email alerts
|

Training the gynecologic oncologists of the future – challenges and opportunities

Ben-Lawrence Kemah,
Nanak Bhagat,
Aayushi Pandya
et al.

Abstract: Several recent advances in gynecologic cancer care have improved patient outcomes. These include national screening and vaccination programs for cervical cancer as well as neoadjuvant chemotherapy for ovarian cancer. Conversely, these advances have cumulatively reduced surgical opportunities for training creating a need to supplement existing training strategies with evidence-based adjuncts. Technologies such as virtual reality and augmented reality, if properly evaluated and validated, have transformative pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The modest differences found may be due to a small number of randomized controlled trials in the data set indicating a need for more high-quality RCTs with larger sample sizes, but regardless, even small findings remain relevant in the field of simulation [3 & ]. A review of surgical simulation in gynecologic oncology found a paucity of data for the validity or reliability of models and programs in their field, additionally supporting the call for additional simulation research [5].…”
Section: Introductionmentioning
confidence: 99%
“…The modest differences found may be due to a small number of randomized controlled trials in the data set indicating a need for more high-quality RCTs with larger sample sizes, but regardless, even small findings remain relevant in the field of simulation [3 & ]. A review of surgical simulation in gynecologic oncology found a paucity of data for the validity or reliability of models and programs in their field, additionally supporting the call for additional simulation research [5].…”
Section: Introductionmentioning
confidence: 99%